Sunflower Tanzania: Climate change risks and opportunities - Groot, Annemarie; Demissie, Teferi Dejene; Duku, Confidence; Budding-Polo, Monserrat; Kabuka, Godfrey; Nkenja, Emanuel; Ninga, Kasian; Lyimo, Raymond; Recha, John W.M.; Osumba, Joab J.L.; Schonenberg, Pierre (2019)
In Tanzania 6% of the land under production is used for the cultivation of sunflower. In areas like Mbeya (Southern Highlands) and Dodoma and Singida (Central Corridor), the area under sunflower varies from 1 - 10 acres per household. According to FAO, the average yield of sunflower is 979 kilogram per hectare. In 2013 sunflower seed production in Tanzania reached approximately 1 million tonnes cultivated by over 2.5 million smallholder farmers.This has the potential to increase productivity and incomes of farmers in the future (CIAT & World Bank, 2017). Despite the relatively good production and business environment for producing sunflower, Tanzania remains a net importer of edible cooking oil. The sunflower oil produced by local processors only meets 40% of the national cooking oil requirements (Zhihua Zeng, 2017).